Auditors and regulatory work (1987–2013): From reporting accountants' to skilled persons' reports in the UK. Issue 7 (17th September 2019) - Collins, David; Dewing, Ian; Russell, Peter
Abstract : Purpose: The purpose of this paper is to investigate the jurisdictional expansion of audit into the area of UK financial regulation. The paper draws on the analytical framework of new audit spaces (Andon et al., 2014, 2015), which built on the concept of regulatory space (Hancher and Moran, 1989), and characterises this new audit space as regulatory work. Design/methodology/approach: Through an intensive reading of a variety of publicly available documentary sources, the paper investigates the role of auditors and accountants in the reporting accountants' and skilled persons' regimes in the UK under the Banking Act 1987 and the Financial Services and Markets Act 2000. Findings: The paper identifies a new audit space characterised as regulatory work, which is made up of three distinct phases (and suggests the recent emergence of a fourth phase), and considers the extent to which these phases of regulatory work share common themes across new audit spaces identified by Andon et al. (2015) as independence, reporting, accreditation and mediating. Originality/value: The paper identifies a further jurisdictional expansion of audit into a new audit space, characterised as regulatory work.